2018
DOI: 10.5897/jabsd2018.0322
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis for grain yield and yield related traits in maize (Zea mays L.) inbred lines in line tester mating design

Abstract: Maize is one of the most important cereal crop widely grown in the world. Maize crosses along with similar maturing checks were evaluated at Hawassa in 2015 to 2016 cropping season to understand the nature of gene action governing yield and its attributes through line × tester analysis and to study genetic contribution of line, tester and the interaction of line × tester to total variation. The experiment was done using α-lattice design 6 × 11 arrangement. Cross L 31 ×T 2 showed the highest mean grain yield th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 4 publications
2
4
0
Order By: Relevance
“…While the hybrid (5 × 4) showed the highest positive and significant effect of SCA of plant height and upper ear height. These results are consistent with [9], [10], [8], [7], [11] findings.…”
Section: Resultssupporting
confidence: 92%
“…While the hybrid (5 × 4) showed the highest positive and significant effect of SCA of plant height and upper ear height. These results are consistent with [9], [10], [8], [7], [11] findings.…”
Section: Resultssupporting
confidence: 92%
“…62×SC 130) had significant negative SCA effects for ear height indicating that these crosses are the best combinations for lower ear placement. This discovery is consistent with the outcome reported by Chemada et al, (2015), Ahmed et al, (2017), Natol (2017) Abebe et al, (2018),and Alsebaey et al, (2021 who reported both positive and negative significant SCA for Silking date, Plant height and ear height.…”
Section: Specific Combining Ability Effectssupporting
confidence: 91%
“…2031 (66.5 and 67.17 days), while six crosses showed significantly higher earliness than both checks TWC 321 and TWC 324 for all crosses were significantly earlier (62.7 to 63.6 days) than the check hybrids TWC 321and TWC 324 (65.33 and 67.00 days). The combining ability of maize inbred lines and concluded that the crosses outperformed the best standard check was investigated (Natol, 2017;Abebe et al, 2018). In the present study regarding the plant height, crosses ranged from 234.33 to 260.44 cm compared to crosses SC 10 and SC 2031 (289.67 and 285.67 cm), crosses ranged from 224.11 to 252.22 cm compared to crosses three way crosses 321 and 324 (272.67 and 263.33 cm).…”
Section: Mean Performancementioning
confidence: 99%
“…General combining ability (GCA) and specific combining ability (SCA) may have positive and negative effects. Positive means that the inbred lines or the hybrids are better than the negative ones (even have the same traits), while negative means that the inbred lines or the hybrids, with the same characteristics, are inadequate in comparison with the positive ones (Karim et al, 2018;Natol, 2017;Rani et al, 2018). The problem in assembling maize hybrid varieties is the proper selection of inbred lines.…”
Section: Introductionmentioning
confidence: 99%